Theodor W. Adorno: cidadania e direito. para uma crítica do capitalismo e do sujeito de direito - Pereira, Luiz Ismael (2013)
This paper discusses the work of Theodor W. Adorno, a member of the School of Frankfurt in what has to contribute to the study of law and citizenship. The Frankfurt School, a philosophical group formed by members of different backgrounds, had as main attribute the development of critical theory of society. Adorno was influenced each other and influenced many colleagues to the Institute for Social Research, but stood out for an original production: gloomy, pessimistic, confident in the performance of the theory linked to practice. His political philosophy related studies are linked to the study of the total administered society, the result of cultural industry and the total art, which influenced the separation of the individual life policy. The Nazi state and anti-Semitism is linked to the contradictions of capitalism. In industrial society democracy alienates the subject does not produce the expected human emancipation with the clarification. Finally, his criticism of human rights and legal form, although recognized as unfulfilled did not stride for human emancipation, allowing a connection to the Marxist thinker Evgeni Pachukanis get the release of his thought.